(untitled) (Annals of Medical Research, 2023)
Aim: The effects of implant locations and prosthesis design (palate less, full palate) on stress values of the implant and bone in maxillary overdenture prostheses were examined and compared with finite element analysis. Materials and Methods: Full palate and palate less four implant supported finite element overdenture models have created with different implant locations (bilateral lateral-1. premolar, canine- 2. premolar, 1. premolar -1. Molar). Static loads have applied with food stuff method on 1. Molar region. Von mises stress on implants and implant parts, maximum and minimum principal stress generated in peri-implant bone have calculated with finite element analysis method (FEA). Results: As a result, it was observed that the palate less design creates more stress on the implants and bone compared to the full palate design. In addition, stress formation was observed to be higher in models with implant positions are posterior. Conclusion: In implant supported overdentures (ISO), palatal coverage ensures more balanced distribution of stresses occurring around the implants and implant parts, regardless of the location of the supporting implants.